Evaluation of surface integrity of root end cavities prepared using conventional and piezoelectric devices: A scanning electron microscopy study - Mithra N Hegde; Manjiri Nagesh Honap; Sreenath Narayanan (Wolters Kluwer Medknow Publications, 2019)
Introduction: An array of factors control the success of endodontic surgery. One of them is the technique used to prepare the root end cavities which is conventionally being done with burs. In past decades, ultrasonic instruments have been introduced for the same. Studies comparing these instruments on root surface integrity are scarce. Thus, an in-vitro Scanning Electron Microscopy study was designed to evaluate the surface integrity of root end cavities prepared using conventional and piezoelectric devices. Methodology: Twelve single-rooted human intact mandibular premolar teeth were endodontically treated and included in the study. They were divided into two groups. In the first group, 3 mm root-end cavities were prepared using conventional retro preparation burs and in the second group, 3 mm root-end cavities were prepared using piezoelectric retro-tips. The specimens were coded for blind evaluation and analysed under scanning electron microscope at 100x, 500x and 1000x magnification for smear layer and debris. Gutmann's scoring criteria was followed to score the specimens. Statistical analysis was carried out using Shapiro Wilk test and the independent sample t-test was used to check mean differences between variables. Results: It was noted that significant statistical differences existed in mean debris and smear layer scores (p< 0.001) between the two groups. In the piezoelectric group, significantly lower debris layer and smear layer was found, compared to the conventional bur group. Conclusion: Root-end cavities prepared using piezo retrotips produced cleaner, well-centered and more conservative surface with minimal debris & smear layer, compared to root-end cavities prepared using conventional burs.